2007
DOI: 10.4049/jimmunol.179.8.5483
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Enhances IL-6 Production in Human Synovial Fibroblast via an AdipoR1 Receptor, AMPK, p38, and NF-κB Pathway

Abstract: Articular adipose tissue is a ubiquitous component of human joints, and adiponectin is a protein hormone secreted predominantly by differentiated adipocytes and involved in energy homeostasis. We investigated the signaling pathway involved in IL-6 production caused by adiponectin in both rheumatoid arthritis synovial fibroblasts and osteoarthritis synovial fibroblasts. Rheumatoid arthritis synovial fibroblasts and osteoarthritis synovial fibroblasts expressed the AdipoR1 and AdipoR2 isoforms of the adiponectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
222
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(241 citation statements)
references
References 47 publications
15
222
1
3
Order By: Relevance
“…39 Our results showed that genistein induced adiponectin production but downregulated p38, p65 and IL-6. These results suggest that genistein may downregulate the negative effects adiponectin by inhibiting p38 and NF-kB pathways.…”
Section: Discussionmentioning
confidence: 56%
“…39 Our results showed that genistein induced adiponectin production but downregulated p38, p65 and IL-6. These results suggest that genistein may downregulate the negative effects adiponectin by inhibiting p38 and NF-kB pathways.…”
Section: Discussionmentioning
confidence: 56%
“…Yet, despite these studies, the role of AMPK in immunity is not exclusively anti-inflammatory. Addition of the AMPK inhibitor Compound C suppressed IFN-␤ induction in response to cytosolic nucleic acids (39) and IL-6 secretion in response to adiponectin (62), showing that AMPK can also induce a pro-inflammatory response in certain instances.…”
Section: Discussionmentioning
confidence: 99%
“…While clear evidence derived from knockdown of adiponectin's specific receptors (Adipo R1 and Adipo R2) shows that immunomodulatory actions of adiponectin are mediated through these receptors [38,39], we believe that LPS contamination may contribute under certain circumstances and should be considered. Several other factors are now recognized as contributing to the emerging complexity of adiponectin's immunomodulatory signalling.…”
Section: Discussionmentioning
confidence: 99%